The use of hybrid-selected template increases the specificity of the polymerase chain reaction. - Lucas, W T; Youngner, J S (Genome Research, 1992)
An efficient method for generating full-length DNA sequences from apparently unsuccessful polymerase chain reactions (PCR) has been developed. In cases where nonspecific background interferes with detection of the PCR product, a second amplification is performed using a nested set of primers. The internal fragment of DNA amplified in this reaction is then blotted to a membrane and used to hybrid-select the desired DNA from the initial amplification. This DNA is eluted and used as the template for a third round of PCR. The re-use of the original primers from the initial reaction enables the final PCR to generate full-length DNA. This technique was used to clone a full-length gene segment 8 from a mutant influenza A/WSN/33 (H1N1) virus after initial PCR attempts had failed.
10.1101/gr.2.1.41